Genetic Etiologies in Developmental and/or Epileptic Encephalopathy With Electrical Status Epilepticus During Sleep: Cohort Study - Gong, Pan; Xue, Jiao; Jiao, Xianru; Zhang, Yuehua; Yang, Zhixian (Frontiers in Genetics, 2021)
Background Recently, the electroencephalogram pattern of electrical status epilepticus during sleep (ESES) had been reported in some genetic disorders, and most of them were noted with developmental and epileptic encephalopathy (DEE) or epileptic encephalopathy (EE). This study aimed to determine the genetic etiologies and clinical characteristics of ESES in DEE/EE. Methods We performed a cohort study in cases of DEE or EE with ESES. Tio-based genetic testing was performed in 74 cases and was analyzed to identify underlying variants. Results Pathogenic or likely pathogenic variants were identified in 17/74 cases, including KCNQ2 (n = 6), KCNA2 (n = 5), GRIN2A (n = 3), SLC9A6 (n = 1), HIVEP2 (n = 1), and RARS2 (n = 1). Eleven were boys. The median age at seizure onset was 6 months. ESES occurred at the mean age of 2.0 ± 1.2 years, predominant in the Rolandic region in 14 years. Twelve of 17 cases had the first stage of different epilepsy preceding ESES: 2/12 were diagnosed as Ohtahara syndrome, 2/12 were diagnosed as infantile spasms, 3/12 were diagnosed as DEE, and 5/12 were diagnosed as EE without the epileptic syndrome. Conclusion Monogenic variants explained over 20% of DEE/EE with ESES. ESES could be an age-related feature in genetic disorders and occurred after the first stage of different epilepsy. Both age-related factors and genetic etiology were suggested to play a role in the occurrence of ESES in genetic DEE/EE.